SUBSURFACE ICE AS A MICROBIAL HABITAT - Mader H.M.; Pettitt M.E.; Parkes R.J.; Wadham J.L.; Wolff E.W. (My University, 2006)
We determine the physicochemical habitat for microorganisms in subsurface terrestrial ice by quantitatively constraining the partitioning of bacteria and fluorescent beads (1-10 μm) between the solid ice crystals and the water-filled veins and boundaries around individual ice crystals. We demonstrate experimentally that the partitioning of spherical particles within subsurface ice depends strongly on size but is largely independent of source particle concentration. Although bacteria are shown consistently to partition to the veins, larger particles, which would include eukaryotic cells, become trapped in the crystals with little potential for continued metabolism. We also calculate the expected concentrations of soluble impurities in the veins for typical bulk concentrations found in natural ice. These calculations and scanning electron microscope observations demonstrate a concentrated chemical environment (3.5 M total ions at -10 °C) in the veins, where bacteria were found to reside, with a mixture of impurities that could sustain metabolism. Our calculations show that typical bacterial cells in glacial ice would fit within the narrow veins, which are a few micrometers across. These calculations are confirmed by microscopic images of spherical, 1.9-μm-diameter, fluorescent beads and stained bacteria in subsurface veins. Typical bacterial concentrations in clean ice (102-103 cells/mL) would result in concentrations of 106-108 cells/mL of vein fluid, but occupy only a small fraction of the total available vein volume (<0.2%). Hence, bacterial populations are not limited by vein volume, with the bulk of the vein being unoccupied and available to supply energy sources and nutrients. © 2006 Geological Society of America.
Keywords: BACTERIA; BACTERIAL HABITAT; EUKARYOTE; GLACIER; ICE; WATER VEINS